2018
DOI: 10.1186/s12870-018-1551-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of GmMYB118 responses to drought and salt stress

Abstract: BackgroundAbiotic stress severely influences plant growth and development. MYB transcription factors (TFs), which compose one of the largest TF families, play an important role in abiotic stress responses.ResultWe identified 139 soybean MYB-related genes; these genes were divided into six groups based on their conserved domain and were distributed among 20 chromosomes (Chrs). Quantitative real-time PCR (qRT-PCR) indicated that GmMYB118 highly responsive to drought, salt and high temperature stress; thus, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(113 citation statements)
references
References 61 publications
0
113
0
Order By: Relevance
“…In this study, we identified a MYB transcription factor, RhMYB108, as being involved in the interplay between ethylene and JA signaling and thus regulating petal senescence in rose. According to their number of conserved MYB structural motifs, MYB proteins are classified into R1-MYB, R2R3-MYB, R3-MYB, and R4-MYB subfamilies 27,28 and function in the regulation of plant growth, hormone signal transduction, stress and disease resistance, and secondary metabolism [29][30][31][32][33] . Here, we show that RhMYB108, which belongs to the R2R3-MYB family, is intensely expressed in rose petals.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified a MYB transcription factor, RhMYB108, as being involved in the interplay between ethylene and JA signaling and thus regulating petal senescence in rose. According to their number of conserved MYB structural motifs, MYB proteins are classified into R1-MYB, R2R3-MYB, R3-MYB, and R4-MYB subfamilies 27,28 and function in the regulation of plant growth, hormone signal transduction, stress and disease resistance, and secondary metabolism [29][30][31][32][33] . Here, we show that RhMYB108, which belongs to the R2R3-MYB family, is intensely expressed in rose petals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant progress has been made in the utilization of CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeat/CRISPR-associated protein 9) system for genome editing and functional studies in various crops. CRISPR-only transformed plants (Du et al, 2018). In recent years, before commencing the whole-plant soybean mutagenesis, the CRISPR/Cas9 constructs functionality are assessed by transient expression in the hairy roots (Do et al, 2018;Curtin et al, 2018), thus strengthening the realization of hairy roots as an excellent transgenic model system for soybean transformation/mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the simultaneous mutagenesis toward all these genes resulted in the formation of transgenic plants with white nodules (a nitrogen deficiency phenotype) [32]. The expression of the GmMYB118 gene increased the drought and salt tolerance of soybean plants, while CRISPR-transformed plants had reduced tolerance, accompanied by higher levels of reactive oxygen species (ROS) and malondialdehide (a marker of oxidative stress) [11]. Investigations with knockout mutants revealed the role of broad spectrum resistance 1 (BSR1) genes in the defense system of rice toward the blast fungus [33], while the mutations in the VvWRKY52 gene from the WRKY TF family revealed its role in the resistance of grape toward Botrytis cinerea that causes rot on the grape's fruits [34].…”
Section: Crispr/cas9 System: Toward Genome Editing In Plant In Vitro mentioning
confidence: 99%
“…Therefore, the elucidation of these steps is achieved by multi-omics, coexpression, and integrated network analysis, revealing the correlation between genes, proteins and metabolites [10]. In the era of genome editing, the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated 9) technology has been used to modify the genes that regulate important biosynthetic pathways in plant in vitro systems aiming to enhance the plant SMs biosynthesis through targeted mutagenesis [11,12]. Metabolomics has been developed as a useful tool for direct chemical insight of the metabolites in heterogenous samples, and as a fundamental part of the current "omics" technologies [13].…”
Section: Introductionmentioning
confidence: 99%